2005
DOI: 10.1002/jqs.930
|View full text |Cite
|
Sign up to set email alerts
|

Re‐interpretation of the Meikirch pollen record, Swiss Alpine Foreland, and implications for Middle Pleistocene chronostratigraphy

Abstract: The Meikirch drilling site in the Swiss Midlands north of Bern is re-interpreted using a combination of sedimentological logging, pollen analyses and luminescence dating. The sedimentary sequence comprises about 70 m of lacustrine deposits, overlain by about 39 m of coarse glacial outwash interpreted to represent at least two independent ice advances. Pollen analyses of the apparently complete limnic sequence reveal a basal late glacial period followed by three warm phases that are interrupted by two stadial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 34 publications
3
59
0
3
Order By: Relevance
“…Unfortunately, the scarcity of material did not allow to cross check the results of ICP-MS by high-resolution g-spectrometry leaving some uncertainty if the investigated sediment are in radioactive equilibrium. However, reports from previous studies have demonstrated that lacustrine sediment is apparently not affected by disequilibrium as long as contents of organic matter and primary carbonates are low, both originating from increased bioproductivity (Lang and Zolitschka, 2001;Thomas et al, 2003;Preusser et al, 2005). Since Lake El'gygytgyn shows relatively low contents of organic material it is unlikely that correct dose rate determination is affected by this problem.…”
Section: Dose Rate Determinationmentioning
confidence: 97%
“…Unfortunately, the scarcity of material did not allow to cross check the results of ICP-MS by high-resolution g-spectrometry leaving some uncertainty if the investigated sediment are in radioactive equilibrium. However, reports from previous studies have demonstrated that lacustrine sediment is apparently not affected by disequilibrium as long as contents of organic matter and primary carbonates are low, both originating from increased bioproductivity (Lang and Zolitschka, 2001;Thomas et al, 2003;Preusser et al, 2005). Since Lake El'gygytgyn shows relatively low contents of organic material it is unlikely that correct dose rate determination is affected by this problem.…”
Section: Dose Rate Determinationmentioning
confidence: 97%
“…Attempts have been made recently to solve this controversy by applying 10 Be surface exposure dating on erratic boulders in the Jura Mountains by , yet with limited success, as the oldest dated boulders date into MIS 6 but are interpreted to have been deposited much earlier. Various novel dating techniques based on luminescence and cosmogenic nuclides have been applied to sediments in Meikirch (Preusser et al, 2005) and its vicinity (Dehnert et al, 2010), and these studies do suggest that the penultimate glaciation was more extensive than the LGM. In any case, the till at Niederbuchsiten does very likely not document the oldest extensive glaciation, because it overlies fluvioglacial sediments that were deposited after an even earlier glacial advance and the respective denudational event.…”
Section: Ages In Chronological Contextmentioning
confidence: 99%
“…The major limitation of this approach, apart from methodological uncertainties, is limited experience in dating sediments older than 150 ka. Initial studies imply that the method may be used up to 250 ka (Preusser et al 2005;Preusser and Fiebig 2009), and possibly beyond. However, this will need to be validated by systematic methodological investigations.…”
Section: Approaches To Constrain the Age Of Overdeepeningmentioning
confidence: 99%